2011
DOI: 10.1080/17533015.2010.551717
|View full text |Cite
|
Sign up to set email alerts
|

Let's Keep Moving: A dance movement class for older women recently relocated to a continuing care retirement community (CCRC)

Abstract: Objective: The purpose of this study was to understand what is was like for older women (78-92 years of age) who recently relocated to a continuing care retirement community (CCRC) to participate in a five-week dance/dance movement therapy (DMT) class called Let's Keep Moving. Dance and DMT have many quality of life benefits for a range of populations (i.e. people with Parkinson's disease) but little is known about how dance/DMT might be beneficial for older adults as they adjust to relocation. Method: A pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(24 reference statements)
2
9
0
2
Order By: Relevance
“…In contrast, the men described sport and leisure-time physical activities as enjoyable pursuits. Like previous studies, we found that the men emphasised the physical pleasure (Minello and Nixon 2017;Phoenix and Orr 2014), psychological benefits (Bidonde, Goodwin and Drinkwater 2009;Grant 2012;Kluge et al 2012;Minello and Nixon 2017) and social connections (Evans and Sleap 2012;Grant 2012;Lozano-Sufrategui et al 2017) their sporting and leisure activities engendered. In line with previous research (Hurd 1999;Minello and Nixon 2017;Phoenix 2010;Pike 2012), the men spoke with great pride about how their physical pursuits and abilities set them apart from less-active, fourth-age others who were perceived to not be ageing as well.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the men described sport and leisure-time physical activities as enjoyable pursuits. Like previous studies, we found that the men emphasised the physical pleasure (Minello and Nixon 2017;Phoenix and Orr 2014), psychological benefits (Bidonde, Goodwin and Drinkwater 2009;Grant 2012;Kluge et al 2012;Minello and Nixon 2017) and social connections (Evans and Sleap 2012;Grant 2012;Lozano-Sufrategui et al 2017) their sporting and leisure activities engendered. In line with previous research (Hurd 1999;Minello and Nixon 2017;Phoenix 2010;Pike 2012), the men spoke with great pride about how their physical pursuits and abilities set them apart from less-active, fourth-age others who were perceived to not be ageing as well.…”
Section: Discussionsupporting
confidence: 84%
“…Some studies point to specific health and functional benefits that participants perceive result from their activities, such as improved balance, strength and flexibility (Bidonde, Goodwin and Drinkwater 2009). Older adults have also reported psychological health benefits from physical activity engagement, including the ability to cope better with stress (Bidonde, Goodwin and Drinkwater 2009;Minello and Nixon 2017), an improved sense of self (Kluge et al 2012) and enhanced quality of life (Grant 2012). Others have found that older adults consider physical activity to be an important tool for combating the general physical decline they associate with being old (Hudson, Day and Oliver 2015;Lozano-Sufrategui et al 2017).…”
Section: Subjective Experiences Of Physical Activity In Later Lifementioning
confidence: 99%
“…In studies conducted in senior homes, it was found that DMT with older people with dementia contributes to cognitive, motor, and social functioning (Hokkanen et al, 2008;Duignan et al, 2009;Karkou and Meekums, 2017). For those moving into sheltered housing, DMT contributes to an increased sense of belonging, emotional well-being, and social involvement (Kluge et al, 2012). Similarly, several studies found that DMT interventions contribute positively to older adults with mental health disorders (Jiménez et al, 2019), whereas DMT's contribution to the well-being of older adults living in the community (not in homes for the elderly) has not been examined to date.…”
Section: Dancing In Old Age and The Uniqueness Of Dance/movement Therapymentioning
confidence: 99%
“…In one project, choir participation for black students in a predominantly white college environment is described as a key mechanism through which academic success can be enhanced (Strayhorn, 2011). Arts participation can also increase access to symbolic assets including familiarity with artists and artistic lifestyles (Kluge et al, 2012;Meeks et al, 2018;Southcott & Joseph, 2015). Some projects also address the limitations of spaces and places by exploring local economic and political circumstances (McAvinchey, 2016;Payson, 2018;Veal, 2017).…”
Section: Extending Network Trust and Safetymentioning
confidence: 99%